Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Sure! Let's walk through the program step by step and see the detailed solution.
1. We initialize two variables [tex]\( A \)[/tex] and [tex]\( B \)[/tex] with [tex]\( A = 0 \)[/tex] and [tex]\( B = 1 \)[/tex].
2. We print the initial values of [tex]\( A \)[/tex] and [tex]\( B \)[/tex]. Thus, the first line of output is:
```
0 1
```
3. We then enter a `FOR` loop that iterates from [tex]\( I=1 \)[/tex] to [tex]\( I=5 \)[/tex]. During each iteration, the following steps take place:
- Calculate [tex]\( C = A + B \)[/tex]
- Print the new value of [tex]\( C \)[/tex]
- Update [tex]\( A \)[/tex] with the current value of [tex]\( B \)[/tex]
- Update [tex]\( B \)[/tex] with the current value of [tex]\( C \)[/tex]
Now, let's go through each iteration in detail.
Iteration 1 ([tex]\( I = 1 \)[/tex]):
- Initial values: [tex]\( A = 0 \)[/tex], [tex]\( B = 1 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 0 + 1 = 1 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
1
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 1 \)[/tex]
- [tex]\( B \leftarrow 1 \)[/tex]
Iteration 2 ([tex]\( I = 2 \)[/tex]):
- Initial values: [tex]\( A = 1 \)[/tex], [tex]\( B = 1 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 1 + 1 = 2 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
2
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 1 \)[/tex]
- [tex]\( B \leftarrow 2 \)[/tex]
Iteration 3 ([tex]\( I = 3 \)[/tex]):
- Initial values: [tex]\( A = 1 \)[/tex], [tex]\( B = 2 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 1 + 2 = 3 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
3
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 2 \)[/tex]
- [tex]\( B \leftarrow 3 \)[/tex]
Iteration 4 ([tex]\( I = 4 \)[/tex]):
- Initial values: [tex]\( A = 2 \)[/tex], [tex]\( B = 3 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 2 + 3 = 5 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
5
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 3 \)[/tex]
- [tex]\( B \leftarrow 5 \)[/tex]
Iteration 5 ([tex]\( I = 5 \)[/tex]):
- Initial values: [tex]\( A = 3 \)[/tex], [tex]\( B = 5 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 3 + 5 = 8 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
8
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 5 \)[/tex]
- [tex]\( B \leftarrow 8 \)[/tex]
Finally, combining all the printed outputs, we get:
```
0 1
1
2
3
5
8
```
This is the step-by-step output of the program.
1. We initialize two variables [tex]\( A \)[/tex] and [tex]\( B \)[/tex] with [tex]\( A = 0 \)[/tex] and [tex]\( B = 1 \)[/tex].
2. We print the initial values of [tex]\( A \)[/tex] and [tex]\( B \)[/tex]. Thus, the first line of output is:
```
0 1
```
3. We then enter a `FOR` loop that iterates from [tex]\( I=1 \)[/tex] to [tex]\( I=5 \)[/tex]. During each iteration, the following steps take place:
- Calculate [tex]\( C = A + B \)[/tex]
- Print the new value of [tex]\( C \)[/tex]
- Update [tex]\( A \)[/tex] with the current value of [tex]\( B \)[/tex]
- Update [tex]\( B \)[/tex] with the current value of [tex]\( C \)[/tex]
Now, let's go through each iteration in detail.
Iteration 1 ([tex]\( I = 1 \)[/tex]):
- Initial values: [tex]\( A = 0 \)[/tex], [tex]\( B = 1 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 0 + 1 = 1 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
1
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 1 \)[/tex]
- [tex]\( B \leftarrow 1 \)[/tex]
Iteration 2 ([tex]\( I = 2 \)[/tex]):
- Initial values: [tex]\( A = 1 \)[/tex], [tex]\( B = 1 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 1 + 1 = 2 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
2
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 1 \)[/tex]
- [tex]\( B \leftarrow 2 \)[/tex]
Iteration 3 ([tex]\( I = 3 \)[/tex]):
- Initial values: [tex]\( A = 1 \)[/tex], [tex]\( B = 2 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 1 + 2 = 3 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
3
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 2 \)[/tex]
- [tex]\( B \leftarrow 3 \)[/tex]
Iteration 4 ([tex]\( I = 4 \)[/tex]):
- Initial values: [tex]\( A = 2 \)[/tex], [tex]\( B = 3 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 2 + 3 = 5 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
5
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 3 \)[/tex]
- [tex]\( B \leftarrow 5 \)[/tex]
Iteration 5 ([tex]\( I = 5 \)[/tex]):
- Initial values: [tex]\( A = 3 \)[/tex], [tex]\( B = 5 \)[/tex]
- Calculate [tex]\( C = A + B \Rightarrow C = 3 + 5 = 8 \)[/tex]
- Print [tex]\( C \)[/tex]:
```
8
```
- Update [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
- [tex]\( A \leftarrow 5 \)[/tex]
- [tex]\( B \leftarrow 8 \)[/tex]
Finally, combining all the printed outputs, we get:
```
0 1
1
2
3
5
8
```
This is the step-by-step output of the program.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.